2009
DOI: 10.1007/s00011-009-0047-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the contribution of tumour necrosis factor in oedema formation induced by histamine in the hind paw of the rat

Abstract: There is mounting evidence that tumour necrosis factor (TNF) is involved in the early phase of inflammatory response, but its relation to histamine action is unclear. In this study we examined the effect of drugs interfering with TNF expression (thalidomide) and activity (infliximab) and compared it to that of a H(1)R histamine receptor antagonist (loratadine) in a model of histamine-induced rat hind-paw oedema formation. Systemic administration of all three drugs effectively reduced the oedema formed by the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
1
5
0
2
Order By: Relevance
“…The processes in the early phase (0 to 15 min) are related to the release of histamine, serotonin, and bradykinin [20]. The study confirmed that histamine injection in the rat paw results in vasodilation and increased vascular permeability due to activation of the endothelial H1 receptors [21]. The results allow us to postulate that the effect of DB on the early stage of inflammation could be related to inhibition of synthesis, release or action of histamine.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The processes in the early phase (0 to 15 min) are related to the release of histamine, serotonin, and bradykinin [20]. The study confirmed that histamine injection in the rat paw results in vasodilation and increased vascular permeability due to activation of the endothelial H1 receptors [21]. The results allow us to postulate that the effect of DB on the early stage of inflammation could be related to inhibition of synthesis, release or action of histamine.…”
Section: Discussionsupporting
confidence: 60%
“…This hypothesis could also explain the observed anti-inflammatory effect of DB during the early stage of histamine-induced rat paw edema. The vascular effects of histamine are mediated by endothelial histamine-H1 receptors [21] and substances, which block these receptors, could influence the early phase of histamine-induced inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…4). Histamine affects the local inflammatory responses via the histamine H 1 receptors (Kalokasidis et al, 2009;Farshid et al, 2011;Arya and Kumar, 2005), and serotonin induces the paw oedema via the serotonin receptors (Sufka et al 1992). Also, LPC, which is biosynthesized by the Land's cycle (Cheng et al, 2009;Shindou and Shimizu, 2009), is a major lipid component of ox-LDL and is implicated in many inflammatory diseases including atherosclerosis (Huang et al, 1999;Kita et al, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…In response to that interaction, vasodilatation and increased vascular permeability occur, thereby allowing the extravasation of plasma proteins and intravascular fluid into the interstitium, with edema formation as a result. In local inflammatory response, polymorphonuclear leukocyte infiltration and cytokine release occur [ 31 , 32 ]. Results of the present study show that the extract prevented the edematogenic effects produced by histamine, which reinforces the assumption of the action on the H 1 receptor.…”
Section: Discussionmentioning
confidence: 99%